Utility of Routine Laboratory Tests for Predicting Gram-Negative Neonatal Sepsis in Low Resources Settings - Akram, Nabeeha Najatee; Ali, Sabah Mohsen; Abdul Raheem, Rasha Sulaiman; Abdulqader, Shaymaa Khalid (Scripta Medica, 2025)
Background: Gram-negative bacteria increasingly recognized as major pathogens in early-onset neonatal sepsis (EONS). Accurate early prediction of causative agents in EONS remains challenging, particularly in resource-limited settings where specific diagnostic markers are lacking. This study evaluates the diagnostic utility of routinely performed laboratory tests in predicting gram-negative bacterial etiology in EONS.Methods: retrospective study included neonates with culture proven EONS who admitted to tertiary hospital in Iraq over 12 months period. Based on result of blood culture, participants divided into 2 groups: (group 1): neonates diagnosed with gram negative bacterial sepsis, while (group 2) involve neonates having positive bacterial growth on blood culture. Clinical characteristics and the results of routine septic screen employed include C-reactive protein and hematologic parameters obtained from complete blood counts compared between both groups. A receiver operating characteristic curve (ROC) was plotted to evaluate the predictive value of routine laboratory tests for Gram-negative sepsis.Results: a total of eighty neonates included in the study, Gram negative bacteria accounted for most bacterial isolates 64 (80%), from which Acinetobacter baumannii was the most frequent isolates 31 (38.8%). C-reactive protein titer was significantly higher in neonate with gram negative bacteria (P value 0.003), while each of absolute neutrophile count and N:L ratio was higher in gram positive bacteria (P value 0.03,0.04 consecutively). On multivariate analysis, CRP was significantly associated with gram negative sepsis and on ROC curve CRP titer at cutoff 19.53 demonstrated excellent prediction of gram-negative EONS with an area under the curve of 0.933 (95% CI: 0.807–1.000; p = 0.009).Conclusion: Most EONS cases were due to gram-negative bacteria, especially Acinetobacter baumannii. High CRP with low ANC and N:L ratio pointed to gram-negative sepsis. CRP >19.5 mg/dl was a strong early predictor for gram negative bacterial growth in blood cultures.
Keywords: Acinetobacter baumannii; C- reactive protein; Neonatal sepsis